The work is wrong because when the student multiplies the second equations he forgets to multiply the -3 with the 4 as well, therefore causing his entire equation to be false.
Work Step by Step
Our two equations are: 1. 5x+4y=2 2. 3x+3y=-3 The student correctly multiplies the first equation by 3 which gives us 15x+12y=-6 However he creates a mistake in the second equation. When multiplying by 4 he forgets to multiply the last -3 with 4. If we correctly multiply, we should get 12x+12y=-12. From there we can subtract 12y from both equations and get 3x=18. Then divide by 3 and we get x=6. Next we plug this back into our original first equation for x to get our y values: 30+4y=2 Solve for y and we get y=-7. We can also check our answer by substituting our answer in the second equation and we end up getting the same value.